Imposto sobre a Renda (IR) e as atividades próprias dos Fundos de Investimento Imobiliários (FIIs) - Martins, Fabrício Aparecido Gomes (2025)
The objective of this work is to study Income Tax (IR) in the activities of Real Estate Investment Funds in Brazil (FIIs), in particular the operations involving the sale of their shares, together with which it provides for exemption from said tax. In view of this, the Tax Authorities reached an understanding regarding the impossibility of the taxpayer using the exemption rule. The issue has been the subject of discussion in the Judiciary Branch, as well as in the Legislative Branch, given the processing of a Bill on the topic